Family and the care of older adults with Alzheimer disease: a scoping review. - de Carvalho Silva, Pedro Victor; Pinto da Silva, Caléo Moisés; Araujo da Silveira, Edilene Aparecida (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2023)
Objective: to identify scientific evidence, in the context of the home, available on family care to elderly people with Alzheimer’s disease. Method: this is a scoping review according to JBI®, through a search strategy in the PubMed, Embase, Cochrane, CINAHL, Web of Science, LILACS and BDENF databases. The analysis of the identified material was performed by three independent reviewers. The extracted data were analyzed and synthesized in a narrative way. Results: of the 1,546 studies found, 17 were kept for review and their content was summarized and divided into ten types of care: 1) Protection and supervision; 2) Hygiene and comfort; 3) Food and hydration; 4) Social and leisure; 5) Oral hygiene; 6) Drug treatment; 7) Communication; 8) Independence; 9) Cognitive exercises; and 10) Pressure injury prevention. Conclusion and implications for practice: there is a lack of studies on the actions carried out by family caregivers and, especially, research on interventions. Care is performed empirically and without professional guidance. It is necessary to invest in research and training for family caregivers.